(untitled) (Hekima Review, 2008)
The article begins with a few biographical details of Paul of Tarsus and moves on to an explanation of the word “Mystery” in general. It then focuses on “Mystery” in Paul with some of its related themes and perspectives. Subsequently, the question: “How is this “mystery” inexorably linked to the self-manifestation of God in the person of Christ for the salvation of the human race?” is taken up for reflection. In dealing with this question the article makes an attempt at contextualizing it in the backdrop of 21st century Christian experience with a special reference to the situation in Africa. The article concludes with the affirmation that the mystery of God in Christ is very much alive and active in the very heart of the world and the challenging mission of hope given to each and every one of us to transform the world.